Pristine and modified biochar applications as multifunctional component towards sustainable future : Recent advances and new insights - Farah Amalina, Ishak; Krishnan, Santhana; Zularisam, Abdul Wahid; Mohd, Nasrullah (Elsevier B.V., 2024)
Employing biomass for environmental conservation is regarded as a successful and environmentally friendly technique since they are cost-effective, renewable, and abundant. Biochar (BC), a thermochemically converted biomass, has a considerably lower production cost than the other conventional activated carbons. This material's distinctive properties, including a high carbon content, good electrical conductivity (EC), high stability, and a large surface area, can be utilized in various research fields. BC is feasible as a renewable source for potential applications that may achieve a comprehensive economic niche. Despite being an inexpensive and environmentally sustainable product, research has indicated that pristine BC possesses restricted properties that prevent it from fulfilling the intended remediation objectives. Consequently, modifications must be made to BC to strengthen its physicochemical properties and, thereby, its efficacy in decontaminating the environment. Modified BC, an enhanced iteration of BC, has garnered considerable interest within academia. Many modification techniques have been suggested to augment BC's functionality, including its adsorption and immobilization reliability. Modified BC is overviewed in its production, functionality, applications, and regeneration. This work provides a holistic review of the recent advances in synthesizing modified BC through physical, chemical, or biological methods to achieve enhanced performance in a specific application, which has generated considerable research interest. Surface chemistry modifications require the initiation of surface functional groups, which can be accomplished through various techniques. Therefore, the fundamental objective of these modification techniques is to improve the efficacy of BC contaminant removal, typically through adjustments in its physical or chemical characteristics, including surface area or functionality. In addition, this article summarized and discussed the applications and related mechanisms of modified BC in environmental decontamination, focusing on applying it as an ideal adsorbent, soil amendment, catalyst, electrochemical device, and anaerobic digestion (AD) promoter. Current research trends, future directions, and academic demands were available in this study.